2014
DOI: 10.1177/039463201402700216
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Distress, Sexual Dysfunction and Relationship Quality in Women with Systemic Sclerosis: Correlation with Clinical Variables

Abstract: To assess the rate of sexual distress, sexual dysfunction and relationship quality and their association with clinical variables in women with systemic sclerosis (SSc), 102 sexually active women with SSc were recruited. Sexual distress, sexual dysfunction and dissatisfaction with relationship quality were investigated by Female Sexual Distress Scale Revised (FSDS-R), Female Sexual Function Index (FSFI) and Dyadic Adjustment Scale (DAS), respectively. The patients underwent medical examinations and nailfold vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 18 publications
0
23
0
4
Order By: Relevance
“…Both baseline and progression of capillary loss were found to be associated with incident SSc-PAH [1,2]. Both studies reported an association between baseline abnormal capillary morphology and incident SSc-PAH [1,2]. No association with incident SSc-PAH was found between capillary dimension nor presence of haemorrhages [1].…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Both baseline and progression of capillary loss were found to be associated with incident SSc-PAH [1,2]. Both studies reported an association between baseline abnormal capillary morphology and incident SSc-PAH [1,2]. No association with incident SSc-PAH was found between capillary dimension nor presence of haemorrhages [1].…”
mentioning
confidence: 96%
“…Both studies reported an association between baseline abnormal capillary morphology and incident SSc-PAH [1,2]. No association with incident SSc-PAH was found between capillary dimension nor presence of haemorrhages [1]. Concerning qualitative assessment, Avouac et al reported worsening to a late NVC pattern over time to be more commonly associated with incident SSc-PAH [1].…”
mentioning
confidence: 99%
See 3 more Smart Citations